SYNTHESIS OF 6-BENZYLAMINOPURINE AND STUDY OF BIOLOGICAL ACTIVE PROPERTIES ON COTTON VARIETY C-6424 PLANTS - Баймуратова Гулбахар Орынбаевна; Насимов Хасан Мурадович; Саиткулов Фозилжон Эргашевич; Хайдаров Гайрат Шойимович, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
6-Benzylaminopurine is a broad-spectrum plant growth regulator, is able to rejuvenate plants, remove plants from dormancy, cause the formation of lateral shoots and root growth, stimulates the formation of chlorophyll and positively affects photosynthesis, making the leaf darker and greener, stronger, in many cultures it is capable of using root treatments of green fruits and berries slightly postpone the maturation period in favor of size and weight.